2019
DOI: 10.1177/1078155219876683
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole prophylaxis in leukemic patients: A retrospective single-center study

Abstract: Background Invasive fungal infections commonly occur in acute myeloid and lymphoblastic leukemia patients receiving chemotherapy. In these patients with acute leukemia, posaconazole prophylaxis is recommended; however, voriconazole may be a less costly alternative. Objectives The objective of this study was to evaluate the efficacy and safety of voriconazole prophylaxis in acute leukemia patients. Methods A retrospective chart review of inpatients at Sunnybrook Health Sciences Centre between 2005 and 2017 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Higher rates of b-IFDs ranging between 5.8% and 8.3% were reported in AML patients receiving AFP with isavuconazole, despite fewer drug–drug interactions (DDIs) [ 50 , 51 , 52 ]. Retrospective analyses reported an incidence for b-IFDs of around 3% in patients with HM receiving AFP with voriconazole [ 53 , 54 ]. Finally, AFP with echinocandin resulted in a high rate of b-IFDs in some studies [ 55 , 56 ], but not in others [ 57 , 58 , 59 ].…”
Section: Invasive Fungal Diseases In Patients Undergoing Remission In...mentioning
confidence: 99%
“…Higher rates of b-IFDs ranging between 5.8% and 8.3% were reported in AML patients receiving AFP with isavuconazole, despite fewer drug–drug interactions (DDIs) [ 50 , 51 , 52 ]. Retrospective analyses reported an incidence for b-IFDs of around 3% in patients with HM receiving AFP with voriconazole [ 53 , 54 ]. Finally, AFP with echinocandin resulted in a high rate of b-IFDs in some studies [ 55 , 56 ], but not in others [ 57 , 58 , 59 ].…”
Section: Invasive Fungal Diseases In Patients Undergoing Remission In...mentioning
confidence: 99%
“…Several retrospective studies have recently evaluated voriconazole in patients with acute leukaemia receiving chemotherapy. 34 , 39–45 One retrospective study ( n = 175) found an incidence of bIFD of 3.3% in the voriconazole arm versus 7.2% in the fluconazole arm. 39 In another study in 241 AML patients receiving (re)induction chemotherapy, bIFD rate was 1.1% in the voriconazole arm, slightly lower than observed with either isavuconazole or posaconazole prophylaxis.…”
Section: Voriconazolementioning
confidence: 99%
“… 34 , 39–45 One retrospective study ( n = 175) found an incidence of bIFD of 3.3% in the voriconazole arm versus 7.2% in the fluconazole arm. 39 In another study in 241 AML patients receiving (re)induction chemotherapy, bIFD rate was 1.1% in the voriconazole arm, slightly lower than observed with either isavuconazole or posaconazole prophylaxis. 34 A study in AML/MDS patients found that a switch to intravenous antifungals was significantly less common in those 471 patients receiving voriconazole prophylaxis (20.6%) versus those receiving fluconazole or itraconazole (30.1%).…”
Section: Voriconazolementioning
confidence: 99%
“…41 In cohort studies of AML patients, the use of voriconazole prophylaxis was associated with an IFD rate of 3-5%. 48,53,54 Due to variable metabolism, CYP2C19 testing prior to commencement could assist with dose selection (please refer to the accompanying optimising antifungal therapy and TDM guidelines by Chau et al 2021 182 , which can be found elsewhere in this supplement). 55,56 Itraconazole Since the 2014 guidelines, a new formulation of itraconazole has been introduced (see later discussion).…”
Section: Voriconazolementioning
confidence: 99%